ANALISIS YURIDIS PENAYANGAN PEMERIKSAAN SAKSI SECARA LANGSUNG DI MEDIA TELEVISI DALAM PERKARA DI PENGADILAN BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA (KUHAP) - Adi Kuangga La Peruntus Sembiring Melial; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
An important part of collecting evidence is the information from a witness. Based on juridical description, a witness is a way or tool which is so important to determine someone was wrong or not in a criminal case. The witness are regulated in the Book of the Code of Criminal Procedure (KUHAP) which is in article 1 number 26 KUHAP. As a one of a democratic Country, Indonesia so concern about a transparency in all sector and “witness in a court was including in this agenda. The principle of Openness was one of the implantation of the transparency Law in Indonesia . The principle of Openness states that a court can be open for public except which regulated in article 153 number 4 which the head of judge at trial shall open the trial and declare it open to the public except in a case concerned with morals or where the accused was legally summoned . But the transpiration of witness was regulated in KUHAP which one about the testimony of witness in Television. In article 185 number 4 was states that separate testimonies of several witness concerning an event or circumstance may be used as legal means of proof if such testimonies are related to one another in such a way as to confirm the occurrence of a certain event or a existence of a certain circumstance.The objectives of this research paper therefore are: first, to know the purpose of broadcasting directly the examination of witness in Television. Second, to know how the reaction from The Indonesian Law on the directly broadcasting the examination witness in Television according to the Book of the Code of Criminal Procedure (KUHAP).The type of this research can be classified in types of juridical normative research, because in this research the authors use the study material libraries like official documents, books for research, in this study, the data source using the primary data, secondary data and tertier data, data collection technique on this research is study of librarianship method or documentary studies.